Tundish permanent lining repairing method

By opening grooves on the surface of the tundra permanent lining and applying silicon sol bonding agent, combined with casting construction castables with silicon micropowder, alumina micropowder, mullite micropowder and high-efficiency water reducer, the permanent lining of the tundra is solved. The problems of cracking and peeling in high temperature-room temperature-high temperature changes have achieved higher degree of bonding and service life.

CN119489183APending Publication Date: 2025-02-21BAOSHAN IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311049867.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The tundra permanent lining is prone to cracking during repeated temperature changes of high-temperature-ambient temperature-high temperature, and the working lining slag line is severely eroded, resulting in permanent lining peeling. The existing repair methods are poor in effect and it is difficult to effectively extend the service life.

Method used

Several grooves are opened in the vertical direction on the surface of the tundra permanent lining, and silicon sol bonding agent is applied. The casting material is used to repair it with a combination of silicon micropowder, alumina micropowder, mullite micropowder and high-efficiency water reducing agent. Rod vibrate the castable to improve the degree of bonding between the old and new linings.

Benefits of technology

It effectively improves the degree of combination of new and old castable materials, extends the service life of the tundra permanent lining, reduces the consumption of retardant materials, and reduces the frequency of use of anchors and insulation boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004403891180000061
    Figure BDA0004403891180000061
  • Figure BDA0004403891180000071
    Figure BDA0004403891180000071
Patent Text Reader

Abstract

According to the tundish permanent lining repairing method, the permanent lining is repaired in a sleeve pouring mode, and in the construction process, the combination between the newly poured permanent lining and the residual lining is increased in the mode that a groove is formed in the surface of the residual lining of the permanent lining and the residual lining is coated with a silica sol binding agent. Silica micropowder, alumina micropowder, mullite micropowder and a high-efficiency water reducing agent are adopted in the bush casting castable combination, so that the water adding amount for construction is reduced, the construction performance is improved, the expansion rate of the bush casting castable after high-temperature burning is increased, the combination degree of a newly-cast permanent lining and a residual lining after bush casting is further improved, and the service life of the bush casting castable is prolonged. And the obtained new casting permanent lining has relatively high density and strength. Through pouring and repairing, the newly-poured permanent lining of the tundish, which is well combined with the residual lining, is formed, so that the residual lining is effectively utilized, the consumption of the castable is greatly reduced, and the service life of the permanent lining is also greatly prolonged. And meanwhile, anchoring parts and heat insulation plates required in the pouring process of the tundish permanent lining are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steelmaking, and in particular relates to a method for repairing a permanent lining of a tundish. Background Art

[0002] The tundish is the last high-temperature container required before the high-temperature molten steel becomes a cast billet in steelmaking production. It is an important platform for achieving stable and efficient continuous casting production. The refractory materials of the tundish include the insulation layer, permanent lining and working lining. The refractory materials of the tundish must meet the requirements of continuous casting of high-temperature molten steel above 1560℃ in multiple furnaces, and its importance is self-evident.

[0003] The refractory material of the tundish working lining is generally made of magnesium coating. After a continuous pouring, the tundish is turned over, the coating is disintegrated, and the tundish continues to be used after the new coating is applied. The permanent lining refractory material will be used repeatedly until the refractory material is severely damaged and no longer used. The permanent lining refractory material includes brick lining and castable lining. Because the castable has good integrity and long service life, the permanent lining is currently mostly castable lining.

[0004] Damage characteristics of the permanent lining of the tundish:

[0005] 1) The permanent lining has to go through repeated temperature changes from high temperature to normal temperature to high temperature, and the castable is prone to cracking;

[0006] 2) The working lining slag line is eroded more, sometimes eroding the permanent lining, and the permanent lining slag line in the injection area is often significantly eroded;

[0007] 3) In the later period of use of the permanent lining slag line and the parts below, due to the enlargement of cracks, repeated erosion and the pulling effect of the disintegration of the working lining coating, there is more peeling, obvious concaveness and thin residual thickness.

[0008] The permanent lining of the tundish generally adopts Al2O3-SiO2 castables. The main problem with the existing castables is that after dozens of furnaces are used, many irregular cracks will appear in the permanent lining. Then, as the number of furnaces used increases, the cracks increase and expand, and there is more peeling in the later period of use.

[0009] When the permanent lining of the tundish has large cracks and peeling, plastic is usually used to repair the large cracks and peeling parts. However, the plastic currently used has low quality and large shrinkage. The repair material often falls off after use. The fallen parts are repaired again with the repair material. The repair material is also easy to sinter with the working lining coating, affecting the disintegration of the coating, and the overall repair effect is poor. Although the average life reaches 800 furnaces, the permanent lining has to be stopped when the anchor is exposed. However, the residual thickness of the castable is greater than 75mm when it is stopped. The plastic repair method is difficult to further increase the life, so all the residual linings have to be removed and the permanent lining is re-cast, which will cause a large consumption of permanent lining refractory materials.

[0010] After a certain degree of use, the remaining lining is removed, the anchors are welded, and the insulation board is pasted. For example, the Chinese patent "CN01132037.0" discloses "a permanent lining castable for a tundish", the weight percentage of which is: 30-75% alumina-grade mullite; 3-67% mullite; 1.5-5% silicon powder; ≤3% cement; 0.1-3% steel fiber, and further includes one or two of 1.5-5% kyanite and 0-5% silica. Improve the thermal shock resistance of the castable, maintain volume stability and sufficient strength.

[0011] Chinese Patent 202211460624.2 discloses "a construction process for casting the permanent layer castable of the intermediate ladle". In this process, it is required to remove and clean the damaged and deteriorated permanent layer castable according to the degree of damage of the permanent layer castable. The "V"-shaped part of the anchor hook must be exposed on the ladle wall and the ladle bottom. The severely damaged parts can be exposed more, and the demolition thickness should be as much as possible to more than half of the original thickness of the permanent layer. The consumption of permanent lining refractory materials is still very large. Summary of the invention

[0012] The purpose of the present invention is to provide a method for repairing a permanent lining of a tundish, which can effectively utilize the residual lining, reduce the consumption of refractory materials, and extend the service life of the permanent lining of the tundish.

[0013] In order to achieve the above object, the present invention provides the following technical solutions:

[0014] A method for repairing a permanent lining of a tundish comprises the following steps:

[0015] 1) When the anchors are exposed on the surface of the permanent lining of the tundish, stop using it and clean the residual paint, slag and residual steel adhering to the surface of the permanent lining;

[0016] 2) A plurality of grooves are provided on the surface of the permanent lining in the longitudinal direction, and the grooves are located away from the anchors of the permanent lining. After the grooves are opened, the floating dust is removed, and then the silica sol binder is applied on the surface of the permanent lining;

[0017] 3) Place the repair mold core into the tundish, inject the castable material for casing construction between the repair mold core and the permanent lining for casing repair construction, and use a vibrating rod to compact the castable material during the casing repair process;

[0018] The castable for cast-in-place construction is obtained by mixing castable, water and high-efficiency water reducing agent evenly; wherein, the amount of water added is not more than 4.5% of the total weight of the castable, and the amount of high-efficiency water reducing agent is not more than 0.2% of the total weight of the castable;

[0019] The castable contains 2-4wt% silicon micropowder, 3-4wt% aluminum oxide micropowder and 2-4wt% mullite micropowder; wherein the particle size of silicon micropowder, aluminum oxide micropowder and mullite micropowder is ≤5μm and the total amount is ≤12wt%;

[0020] 4) After the cast-in repair construction is completed, demoulding shall be carried out after curing for 2 to 4 days, and then curing shall be carried out for another 2 to 3 days after demoulding, and then it shall be put into use after baking.

[0021] Preferably, the groove has a depth of 10 to 15 mm, a width of 20 to 30 mm, and a lateral spacing distance between the grooves of 200 to 250 mm.

[0022] Preferably, the SiO2 content in the silica sol binder is ≥30wt%, and the pH value is ≥9.

[0023] Furthermore, in step 3), the castable composition also includes sintered mullite, special grade coke stone and pure calcium aluminate cement; preferably, the Al2O3 content in the castable is ≥65wt%.

[0024] Furthermore, the linear variation rate of the castable for casing construction after calcination at 1400° C. for 3 hours is +0.3 to +0.6%.

[0025] Furthermore, if the repaired permanent lining of the tundish cracks or peels off during use, the cracked or peeled off parts are repaired with plastic, and the Al2O3 content in the plastic is ≥60wt%.

[0026] Preferably, the linear shrinkage of the plastic material calcined at 1400° C. for 3 hours is no more than 1%.

[0027] The permanent lining of the tundish is deactivated when the anchors are exposed after long-term use, and the residual coating adhering to the surface of the permanent lining is cleaned. Sometimes, the coating of the working lining at the slag line is severely eroded, which may erode the permanent lining and cause the permanent lining to be eroded and concave. In this case, the residual steel and slag at the eroded part of the slag line need to be cleaned.

[0028] Since the exposed anchors have been oxidized, it is meaningless to weld new anchors on them. If the repair mold core is directly put in to cast and repair the permanent lining, there are no anchors in the permanent lining formed by the new castable, so the cast part of the permanent lining and the residual lining (the remaining part after the original permanent lining is corroded) cannot be well combined.

[0029] In order to improve the bonding degree between the new and old castables, the present invention opens a plurality of grooves along the longitudinal direction on the surface of the residual lining. During the casting process, the new castable is injected into the grooves, which increases the bite force between the new cast permanent lining and the residual lining, thereby increasing the bonding degree between the new cast permanent lining and the residual lining. The grooves are opened away from the anchors of the residual lining to avoid damage to the anchors.

[0030] After grooving, use compressed air to clean the surface of the residual lining to remove the floating dust on the surface of the residual lining, so that the silica sol binder can adhere firmly to the surface of the residual lining. The presence of the silica sol binder will further improve the bonding degree between the cast permanent lining and the residual lining. The SiO2 content in the silica sol binder is required to be ≥30wt%, and the pH value is ≥9 to ensure that the silica sol binder has the characteristics of strong bonding and high temperature resistance.

[0031] In the process of repairing and pouring, the present invention adds silicon micropowder: 2-4wt%, aluminum oxide micropowder: 3-4wt%, and mullite micropowder: 2-4wt% to the casting material for casing casting, wherein the particle size of silicon micropowder, aluminum oxide micropowder and mullite micropowder is ≤5μm, and the total amount is ≤12wt%. The casting material contains a certain amount of micropowder, which can be fully filled in the gaps between the casting material particles, so that the particles, fine powder and micropowder are closely combined, greatly reducing the gaps in the casting material, thereby reducing the amount of water added during construction. Compared with ordinary water reducing agents, the addition of high-efficiency water reducing agent to the casting material further reduces the amount of water used, so that the amount of water added during construction is controlled within 4.5%. The less amount of water added during construction can reduce the shrinkage of casing casting material, improve the degree of combination of new lining and old lining after casing casting, improve the compactness of the casting material, and make the strength of the new permanent lining obtained after casing casting higher.

[0032] The present invention adopts a combination of silicon micropowder, alumina micropowder and mullite micropowder, which has a relatively low cost and has a good re-foaming condition during vibration construction, which is beneficial to improving the air removal rate in the casting material during the construction process, so that the newly cast permanent lining has a higher density and strength, and at the same time increases the expansion rate of the casing casting material after high-temperature firing, and improves the bonding degree between the new lining and the old lining. The permanent lining casting material of normal casting construction has a linear change rate of 0 to +0.3% after calcination at 1400°C for 3 hours, and the linear change rate of the casing casting material of the present invention after firing is +0.3 to +0.6%.

[0033] Silica powder has a better water-reducing effect, but it cannot be added too much, otherwise the corrosion resistance of the castable will be affected. In addition to the water-reducing effect, alumina powder can also promote the sintering of castables at high temperatures and improve the strength. However, adding too much alumina powder will increase the viscosity of the castable, and the rebubbling will be poor during vibration construction. The vibration pouring construction of the castable is a process of eliminating the air in the castable and forming a dense construction body. If the bubbles in the castable cannot be completely discharged, it will affect the density of the new permanent lining and cause the strength of the permanent lining to decrease. In addition, the price of alumina powder is relatively high, and adding too much will also increase the cost. Mullite powder can also promote the sintering of castables and improve the strength at high temperatures.

[0034] Since the permanent lining is mainly corroded at and below the slag line, and the permanent lining above the liquid level of the tundish is not corroded, if the core of the normal pouring construction is used for the casing repair, it is difficult to add the castable material between the core and the residual lining from above, and the vibrating rod cannot be inserted. Therefore, the distance between the repair core and the residual lining above the slag line is kept at 40-60mm. If it is less than 40mm, the interval between the core and the residual lining is small, which is not conducive to the addition of castables during casing casting. If it is greater than 60mm, the capacity of the tundish will be greatly reduced after casing casting.

[0035] The plastic material currently used for repairing the permanent lining during use is of low quality, with an Al2O3 content of only 45%, and a linear change rate and shrinkage of more than 3% after high-temperature firing, resulting in a poor repair effect. In order to improve the repair effect of the permanent lining during use, the tundish permanent lining of the present invention is cracked or peeled off during use, and the cracked or peeled parts are repaired with a plastic material, wherein the Al2O3 content of the plastic material is ≥60wt%, and the linear change shrinkage rate is not more than 1% after being calcined at 1400°C for 3h after repair.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention increases the bonding between the newly cast permanent lining and the residual lining by opening grooves on the surface of the residual lining and coating a silica sol binder. The casing casting castable combination adopts silicon micropowder, alumina micropowder, mullite micropowder and high-efficiency water reducing agent, which reduces the amount of water added for construction, increases the expansion performance of the casing casting castable, further improves the bonding degree between the newly cast permanent lining and the residual lining after casing casting, and the air removal rate in the casting material during the construction process is high, so that the newly cast permanent lining obtained has higher density and strength.

[0038] Through the casting repair, a new permanent lining of the tundish with good combination of the newly cast permanent lining and the residual lining is formed, which effectively utilizes the residual lining, reduces the consumption of casting materials, and prolongs the life of the permanent lining. At the same time, it also saves the anchors and insulation boards required in the casting process of the tundish permanent lining, and reduces the labor intensity of removing the residual lining, welding anchors and pasting insulation boards.

[0039] At the same time, the present invention uses plastic to repair cracked and peeled parts during use, further extending the life of the permanent lining. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments.

[0041] The control parameters of the embodiment of the present invention and the comparative example during the casing casting process are shown in Table 1. The other components in the castable are M70 sintered mullite as the main raw material, special grade coke stone as the secondary raw material, and pure calcium aluminate cement as the binder. The properties of the newly cast permanent lining obtained after casing casting are shown in Table 2.

[0042] From the data in Table 2, it can be seen that in Examples 1-5, grooves are made on the residual lining, and silica sol is applied to the surface of the residual lining, which improves the bonding between the newly cast permanent lining and the residual lining. The composite uses silica powder, alumina powder, mullite powder and high-efficiency water reducing agent, and the water addition is controlled within 4.5%, and the newly cast permanent lining has high strength and low porosity.

[0043] In the comparative example 1, no grooves were made on the surface of the residual lining during the casting process, and no silica sol was applied on the surface of the residual lining. The bonding force between the new and old linings was poor, cracks existed between the new and old linings, and the new lining was at risk of falling off.

[0044] The content of alumina in the castables of Comparative Example 2 was relatively low, and the corrosion resistance at the permanent slag lining line was relatively poor.

[0045] Comparative Example 3 did not use mullite powder, and the amount of water added was relatively large. During construction, the castable was relatively sticky, the back foaming was not good, the porosity was high, and the density of the permanent lining was low.

[0046] In Comparative Example 4, the total amount of micropowder is relatively small, the amount of water added is relatively large, the porosity is high, the density of the permanent lining is low, the linear change rate expansion of the castable is small, the bonding between the new and old linings is not good, there are cracks, the new lining has the risk of falling off, and the room temperature strength and high temperature strength are low.

[0047] Comparative Example 5 uses common water reducer, adds more water, has higher porosity, lower density of permanent lining, shrinks linear change rate of castable, and has lower strength at room temperature and high temperature. The high efficiency water reducer used in the present invention is a standard high efficiency water reducer purchased from outside.

[0048] By comprehensively taking the above measures, the newly cast permanent lining obtained by the present invention has good bonding with the residual lining, high strength and good corrosion resistance. The permanent lining is repaired by the sleeve casting method, which reduces the consumption of the casting material and greatly prolongs the life of the permanent lining. During use, plastic is used to repair the cracked and peeled parts, further prolonging the service life of the permanent lining.

[0049] Table 1

[0050]

[0051] Table 2

[0052]

Claims

1. A method for repairing a permanent lining of a tundish, characterized in that: The following steps are involved: 1) When the anchors are exposed on the surface of the permanent lining of the tundish, stop using it and clean the residual paint, slag and residual steel adhering to the surface of the permanent lining; 2) A number of grooves are provided on the surface of the permanent lining in the longitudinal direction, and the grooves are located away from the anchors in the permanent lining; After the groove is opened, remove the floating dust, and then apply silica sol binder on the permanent lining and groove surface; 3) Place the repair mold core into the tundish, inject the castable material for casing construction between the repair mold core and the permanent lining for casing repair construction, and use a vibrating rod to compact the castable material during the casing repair process; The castable for cast-in-place construction is obtained by mixing castable, water and high-efficiency water reducing agent evenly; wherein, the amount of water added is not more than 4.5% of the total weight of the castable, and the amount of high-efficiency water reducing agent is not more than 0.2% of the total weight of the castable; The castable contains 2-4wt% silicon micropowder, 3-4wt% aluminum oxide micropowder and 2-4wt% mullite micropowder; wherein the particle size of silicon micropowder, aluminum oxide micropowder and mullite micropowder is ≤5μm and the total amount is ≤12wt%; 4) After the cast-in repair construction is completed, demoulding shall be carried out after curing for 2 to 4 days, and then curing shall be carried out for another 2 to 3 days after demoulding, and then it shall be put into use after baking.

2. The method for repairing the permanent lining of a tundish according to claim 1, characterized in that: The groove has a depth of 10 to 15 mm and a width of 20 to 30 mm, and a lateral spacing distance between the grooves is 200 to 250 mm.

3. The method for repairing the permanent lining of a tundish according to claim 1, characterized in that: The SiO2 content in the silica sol binder is ≥30wt%, and the pH value is ≥9.

4. The method for repairing the permanent lining of a tundish according to claim 1, characterized in that: In step 3), other components of the castable include sintered mullite, special grade coke and pure calcium aluminate cement; preferably, the Al2O3 content in the castable is ≥65wt%.

5. The method for repairing the permanent lining of a tundish according to claim 1 or 4, characterized in that: The linear change rate of the castable for casing construction after calcination at 1400° C. for 3 hours is +0.3 to +0.6%.

6. The method for repairing the permanent lining of a tundish according to claim 1 or 4, characterized in that: In step 3), the repair mold core is placed in the tundish, and the distance between the repair mold core and the residual lining above the liquid surface is maintained at 40 to 60 mm.

7. The method for repairing the permanent lining of a tundish according to claim 1, characterized in that: The repaired tundish permanent lining is repaired with plastic material at cracked and peeled parts during use, wherein the Al2O3 content of the plastic material is ≥60wt%.

8. The method for repairing the permanent lining of a tundish according to claim 7, characterized in that: The linear shrinkage rate of the plastic material after being calcined at 1400° C. for 3 hours is no more than 1%.

Citation Information

Patent Citations

  • Tundish permanent layer castable pouring construction technology

    CN115889746A

  • Pouring material for permanent liner in middle ladle

    CN1223421C